Fuel Burn Benefits of Altitude Optimization Strategies in the Cruise Phase of LongHaul Flights - Silva, Jorge (2020)
This paper focuses on the vertical profile of the cruise phase of long-haul commercial flights covering legislation, operational standards, communications, surveillance, flight planning and performance aspects. Two case studies are presented: the first one describes and compares an actual vertical profile of a flight and an optimised one, with detailed calculations as well as results estimation; the second one compares two vertical profile optimization procedures strategies. Small modifications in how cruise phase of a flight is operated airlines can achieve cost reductions, mitigate environmental impacts, and contribute to airspace efficiency.